2021
DOI: 10.1186/s12884-021-03932-0
|View full text |Cite
|
Sign up to set email alerts
|

Violence and depression among pregnant women in Egypt

Abstract: Background Depression is a serious mental health disorder that might affect women in the childbearing period. Incidences increase during pregnancy as well as after delivery. Its association with intimate partner violence (defined as physical, sexual, or psychological harm by a current or former partner) has been reported in many countries. Data about this sensitive issue are lacking in Egypt. The aim of the study was to determine the relation between intimate partner violence and depression dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Having domestic violence (general) increases the probability of depression during pregnancy by 9 times, this figure is alarming due to the consequences that this entails and is even higher than that of a study carried out in Brazil that mentioned that women who had suffered a certain type of violence were 6.74 times more likely to present depressive symptoms [33]. Various studies were reviewed in which evidence was obtained that supports the data obtained, one of the studies was carried out in Egypt with pregnant women in which the relationship between violence exerted by couples and depression was evaluated, they found a great association between both variables, in addition to this they found that the most significant type of violence that caused depression was emotional and sexual [34]. Another study carried out in northern Tanzania also found a relevant association between intimate partner violence and depression, in which it coincides with the present study and considers violence, in any of its types, but mainly physical, as a risk factor.…”
Section: Discussionmentioning
confidence: 93%
“…Having domestic violence (general) increases the probability of depression during pregnancy by 9 times, this figure is alarming due to the consequences that this entails and is even higher than that of a study carried out in Brazil that mentioned that women who had suffered a certain type of violence were 6.74 times more likely to present depressive symptoms [33]. Various studies were reviewed in which evidence was obtained that supports the data obtained, one of the studies was carried out in Egypt with pregnant women in which the relationship between violence exerted by couples and depression was evaluated, they found a great association between both variables, in addition to this they found that the most significant type of violence that caused depression was emotional and sexual [34]. Another study carried out in northern Tanzania also found a relevant association between intimate partner violence and depression, in which it coincides with the present study and considers violence, in any of its types, but mainly physical, as a risk factor.…”
Section: Discussionmentioning
confidence: 93%
“…Violence was also more prevalent among women with unintended pregnancies and those experiencing depression, suggesting a significant association between domestic violence and depression during pregnancy [ 49 , 50 ]. The disparities in domestic violence prevalence between Iran and the United States may be attributed to a few key factors, including differences in the measurement tools used to assess domestic violence, variations in sample sizes across studies, as well as the reluctance of women to disclose their experiences of abuse.…”
Section: Discussionmentioning
confidence: 99%
“…It is understood that this situation can lead to serious psychological consequences [ 29 ]. Studies have revealed that prenatal exposure to verbal, psychological and sexual violence has negative effects on newborns [ 33 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, having a large number of children and being polygamous (married to more than one woman) heighten the chances of psychological and verbal violence against women [ 48 ]. Another study found that exposure to verbal and psychological violence during pregnancy is strongly associated with depression [ 58 ].…”
Section: Introductionmentioning
confidence: 99%